Efeitos da emissão dos efluentes domésticos na proliferação de Aeromonas Spp em águas de superfície e pescado do estuário do Rio Bacanga, São Luís - MA - Martins, André Gustavo Lima de Almeida (2005)
This research work was designed to detect the presence of Aeromonas in the Bacanga River estuary, São Luís, Maranhão State, Brazil. The database consisted of 90 samples of the river’s surface water and 30 samples of fish, in the period from March to October, 2004. They were amenable, simultaneously, to counting of bacteria on Agar Gelatin Phosphate Salt (GSP) plus 20μg/mL of ampicilim (UFC/mL or UFC/g) and to the determination of the Most Probable Number (MPN/100mL or MPN/g), through the multiple test-tube technique using the Tripticase Soy Broth (TSB) plus 20μg/mL of ampicilim. The analyzed fish species were: catfish (Pimelodus maculatus), mullet (Mugil cephalus), flatfish (Pleuronectes platessa), golden tetra (Hemigrammus rodwayi) and Atlantic thread-herring (Opisthonema oglinum). The results showed dissemination of Aeromonas in the estuary. The counts for the water and fish samples varied from 40 to 1.3x108 UFC/mL and from 3.2x102 to 5.8x106 UFC/g, respectively, with the highest indices being registered at points next to domestic sewages outlets. The values for the MPN/100mL in water samples varied from 2.3x104 to 1.6x107 and for the MPN/g in fish samples from 230 to 24x103. The occurrence of the greatest indices of Aeromonas in April, at the height of the rainy season, and the lowest in October, at the height of the dry season, suggests there to be a probable seasonality of bacteria density in the studied environment. Out of the 751 isolated strains from water samples, 582 were positive for Aeromonas, being 52.7% A. caviae, 23.8% A. hydrophila, 19.5% A. veronii and 3.7% A. sobria. Out of the ones isolated from the fish (245 strains) 184 were identified as Aeromonas, being 43.4% A. caviae, 28.2% A. hydrophila, 26.6% A. veronii and 1.6% A. sobria. As concerns the physical and chemical parameters measured in surface waters of the Bacanga River’s estuary, temperature, salinity and pH only showed significant correlations. In general, strains of Aeromonas sp. were found to be sensitive to most of the tested antimicrobians, except for ampicillim, to which they showed 100% resistance.